PENINGKATAN KETERAMPILAN PRAKTIK AKUNTANSI MELALUI PEMANFAATAN APLIKASI DIGITAL BAGI SISWA SMK HARAPAN BANGSA - Regita Cahya Pertiwi; Diana Salsa Bila; Dionisia Imbuk; Prisila Damayanty (ASOSIASI IDEBAHASA KEPRI, 2026)
The development of digital technology has driven changes in accounting practices, particularly in the processes of recording and preparing financial statements. This condition requires vocational education institutions, especially Vocational High Schools (Sekolah Menengah Kejuruan/SMK), to adjust their learning approaches in order to align with the needs of the business and industrial sectors. However, accounting learning in SMKs is still largely conducted manually, resulting in students’ practical skills in using digital accounting applications not being optimal. This study aims to improve accounting practical skills through the utilization of the Zahir Accounting digital application for students of SMK Harapan Bangsa. This research is based on various studies and community service activities conducted by researchers from the Institute of Business and Informatics (IBI) Kosgoro 1957, which indicate that the use of digital accounting applications can enhance recording effectiveness, understanding of accounting workflows, and users’ practical skills.The method used in this study is digital application–based accounting practice learning through training and mentoring activities on the use of Zahir Accounting. The expected results of this study are improvements in students’ abilities to record transactions, process financial data, and prepare financial statements in a systematic and computerized manner. This research is expected to contribute to the development of digital-based accounting learning in vocational high schools. Keywords: accounting practical skills, digital accounting application, Zahir Accounting, vocational high school (SMK)